PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK - Arfiana Dewi; Danis Maulana; Ajira Arabi’i; Tri Hanani (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) and profitability on firm value in transportation and logistics companies listed on the Indonesia Stock Exchange during 2020–2023. Firm value is measured using Tobin’s Q, profitability is proxied by Return on Assets (ROA), and CSR is measured using a disclosure index based on financial and sustainability reports. The research uses purposive sampling with 38 observations and employs multiple linear regression analysis after classical assumption testing. The results show that CSR has no significant effect on firm value, indicating that social responsibility disclosures are not yet considered a strong factor by investors. On the other hand, profitability (ROA) has a significant negative effect on firm value, suggesting that lower financial performance may lead to reduced investor confidence. The study provides insights for companies to strengthen financial strategies and CSR communication to increase firm value.